Temporary Threshold Shifts among Iron and Steel Factory Workers in Tanzania: A Pre-Interventional Study - Nyarubeli, Israel P. (Ann Glob Health, 2021)
BACKGROUND: Workers in iron and steel factories in Tanzania are exposed to noise levels above recommended limit values, without using hearing protection devices. Exposure to noise levels above 85 dB(A) is associated with temporary threshold shifts (TTS) of human hearing. Nevertheless, there are few studies of noise and hearing from African countries. OBJECTIVE: To determine whether the normal hearing workers in Tanzania experiences TTS after full-shift occupational noise exposure of 85 dB(A) and above. METHODS: A total of 55 workers were included. Full-shift personal noise measurements were conducted. Pre- and post-shifts pure-tone audiometry were conducted for each worker. TTS was defined as a 10 dB or greater change at 1000, 2000, 3000 or 4000 Hz in either ear. RESULTS: We found that 85.5% of the workers developed TTS across the work shift. There was significant increase in mean hearing thresholds across shift at 1000, 2000, 3000 and 4000 Hz among the workers exposed to an average personal noise exposure (L(Aeq,8h)) of 90.4 dB(A) (SD = 2.7). The difference in mean hearing thresholds was higher at 4000 Hz [Arithmetic Mean (AM) = 10 dB SD = 4 dB] compared to that of 1000 Hz (AM = 4 dB SD = 3 dB), 2000 Hz (AM = 4 dB SD = 4 dB), and 3000 Hz (AM = 9 dB SD = 6 dB), respectively. CONCLUSIONS: Interventions to reduce occupational personal noise exposure are warranted to reduce the high risk of developing a permanent threshold shift with persistent high noise exposure. An intervention study is planned for this group of workers.